The mistaken doctrine of common law: A critique - Lukáš Nikodym; Tomáš Nikodym; Tereza Pušová (DANUBE: Law, Economics and Social Issues Review, 2016)
The study deals with Huerta de Soto's thesis about the "mistaken doctrine of common law", which is based on the equalization of depositum irregulare and mutuum contracts. He concluded that equalization of these contracts resulted in the creation of business cycles. According to this study, Huerta de Soto made a mistake when considering contracts inspired by the continental law based on Roman law. The study shows that mutuum was even in Roman law an ancient contract that was not codified, and that Huerta de Soto's interpretation of this contract in the Anglo-American legal system is based more on civil law, not on common law as he stated in his work. Finally, the problem of common law did not lie in the equalization of the mentioned contracts, but rather in the absence of depositum irregulare contracts applied to monetary questions.
Keywords: 330; Common Law; Roman Law; Business Cycles; Contracts; Law of Bailment